Study on the Acceptance Test Specification of Grid-connected Micro-grid - Le Jian; Tao Mao; Yang Zhichun; Liu Yang; Liu Kaipei (Institute of Advanced Engineering and Science, 2014)
According to relevant standards and specifications at home and abroad, the acceptance tests that must be performed to validate whether the grid-connection/splitting process and grid-connection operation of micro-grid meet the relevant technical requirements have been studied in this paper. Combining the technical requirements of the micro-grid, this paper gives the conditions, measuring instruments, general process and acceptance standards of the acceptance tests, and focuses on the designing of acceptance tests of key operation, operation parameters and protection functions of the micro-grid, such as grid-connection/splitting process, power quality during the grid-connection operation and reverse power and short-circuit protection and so on. The relevant test methods, specific steps and acceptance standards are proposed. This paper can provide a good foundation and basis for designing the acceptance tests specification of micro-grid.